Antioxidant Activity of Cosmos Caudatus Extracts By Using Different Types of Extraction Methods - Nur Afeefa, Mohd Khairi (2013)
The discoveries on new resources of natural antioxidant from plants have attracted increasing interest due to high potential of antioxidant capacity. In this paper, antioxidant activity of Cosmos caudatus extracts was investigated by using different types of extraction methods which were maceration extraction, Soxhlet extraction and ultrasonic-assisted extraction using 70% acetone (v/v) as solvent. The antioxidant activity and ascorbic acid content from each method was determined by 2,2-Diphenyl-1-Picrylhydrazyl (DPPH) assay and High Performance Liquid Chromatography (HPLC) respectively. The results show that the three extraction methods exhibit significant value of ascorbic acid content. Ultrasonic-assisted extraction was the efficient method as it exhibits the highest amount of ascorbic acid content with 26.590 mg ascorbic acid equivalent per 1 g sample (mg AAE/g) with the corresponding value of 42.208% of its antioxidant activity after 60 minutes extraction. This is followed by Soxhlet extraction (13.527 mg AAE/g) and maceration extraction (5.190 mg AAE/g) within 8 hour and 24 hour extraction time respectively. Analysis by HPLC also shows that C. caudatus extract using ultrasonicassisted extraction has the highest vitamin C content (2.440 mg AAE/g) followed by Soxhlet extraction (0.968 mg AAE/g) and maceration extraction (0.739 mg AAE/g). For further study, optimization of the ultrasonic extraction method is proposed to achieve the optimum condition in extracting bioactive compounds from C. caudatus.